Urban farming transformation through a PAR approach: Enhancing production capacity and business management - Ima Aryani; Ratnasari Nur Rohmah; Muhammad Halim Maimun; Sabrina Nur Alifah; Inta Isnaningrum; Efri Roziaty (Community Empowerment, 2026)
Urban farming serves as a strategic solution for strengthening household food security in limited areas. This community service program aims to enhance the hydroponic lettuce production capacity and business management professionalism of the Mutiara Women Farmer Group (KWT) in Surakarta. The methodology employed was Participatory Action Research (PAR), integrating participatory planning, technical cultivation training, bookkeeping mentoring, and digital marketing strategies. The results showed achievements surpassing the initial targets: hydroponic lettuce production significantly increased by 77%, rising from 45 kg to 80 kg per harvest period. Beyond quantity, the harvest quality became more uniform, meeting market standards. Regarding management, KWT members successfully implemented a simple financial recording system and began adopting digital platforms for marketing their produce. This program demonstrates that the synergy between hydroponic technology and institutional strengthening effectively enhances the sustainable economic independence of urban communities.